2014
DOI: 10.1371/journal.pone.0107218
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Immune-Related Genes in Children with Down Syndrome

Abstract: Individuals with Down syndrome (DS) have a high incidence of immunological alterations with increased susceptibility to bacterial and viral infections and high frequency of different types of hematologic malignancies and autoimmune disorders. In the current study, we profiled the expression pattern of 92 immune-related genes in peripheral blood mononuclear cells (PBMCs) of two different groups, children with DS and control children, to identify differentially expressed genes that might be of pathogenetic impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 48 publications
(41 reference statements)
7
26
0
Order By: Relevance
“…We then carried out gene ontology enrichment analysis of each module to gain insight into the biological significance of these clusters of co-expressed genes ( Table S6 ). This analysis confirmed a number of cellular and molecular processes previously found to be altered in DS or mouse model brains, including cell morphogenesis (Module [M] 24; Figure S5A ), RNA processing (M31), gene transcription (M52), immune responses (M54; Figure S5B ), neuronal differentiation (M4 and M45; Figure S6A,D ), synaptic transmission and regulation (M10 and M34; Figure S6B,C ) and electron transport (M14) ( Table S6 ) (Bahn et al, 2002; Lockstone et al, 2007; Sahun et al, 2014; Yoshida et al, 2013; Zampieri et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…We then carried out gene ontology enrichment analysis of each module to gain insight into the biological significance of these clusters of co-expressed genes ( Table S6 ). This analysis confirmed a number of cellular and molecular processes previously found to be altered in DS or mouse model brains, including cell morphogenesis (Module [M] 24; Figure S5A ), RNA processing (M31), gene transcription (M52), immune responses (M54; Figure S5B ), neuronal differentiation (M4 and M45; Figure S6A,D ), synaptic transmission and regulation (M10 and M34; Figure S6B,C ) and electron transport (M14) ( Table S6 ) (Bahn et al, 2002; Lockstone et al, 2007; Sahun et al, 2014; Yoshida et al, 2013; Zampieri et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Because the activity of one's immune system involves many distinctly separate yet cooperative facets of immune function, each of which converge to impact one's risk of extrinsic mortality, even those growing up in safe, benign environments with few external mortality threats are predicted to adopt faster life history strategies if they lack immune competence. Indeed, it has long been known that various genetic problems -from genetic anomalies writ large, such as the presence of extra chromosomes [e.g., trisomy 21 (Heston 1977;Zampieri et al 2013)] to more subtle single-gene / single nucleotide mutations -factor significantly into a large number of immunological problems. As is true for the genetics of height (Allen et al 2010;Wood et al 2014), but to an much greater extent given the tremendously multifaceted nature of immune function, a large number of small variations in numerous relevant alleles may impact outcome when it comes to immune competence, sometimes with suboptimal outcomes.…”
Section: Immune Function: More Than An Intermediary Between Early Lifmentioning
confidence: 99%
“…PmRab7 gene with housekeeping elongation factor 1-alpha gene [26] has shown significantly up-regulated with certain fold changes in the lymphoid tissues with the post WSSV infection till 72 h of post infection. Interestingly, it has reported no significant fold changes found in the PmRab7 expression after WSSV challenge in the earlier study, while it has also been reported that significant upregulation of all GTPase family of gene after WSSV internalization by subtractive hybridization in Penaeus japonicus [27].…”
Section: Discussionmentioning
confidence: 99%